Consider the following equation \(Ax=b\),\[\begin{bmatrix}
1 & 2 & 3 \\
1 & 4 & 9 \\
4 & 5 & 7 \\
\end{bmatrix}x = \begin{bmatrix}
2 \\
4 \\
6 \\
\end{bmatrix}.\] The solution of this equation is,\[x = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix}.\] Now let us suppose we wanted to solve a similar problem ( \(A'x' = b\) )with a slightly perturbed matrix,\[A' = \begin{bmatrix}
1 & 2 & 3 \\
1 & 6 & 9 \\
4 & 5 & 7 \\
\end{bmatrix}.\] Notice that this matrix differs from \(A\) in the (2,2) element (6 instead of 4).
The Sherman-Morrison formula tells us to form \(u = [0~1~0]^T, v = [0~~2~~0]^T\), so that \[A' = A + u v^T.\] Hence \[y = x = A^{-1}b = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix},\text{ and } z = A^{-1} u = \begin{bmatrix}
0.125 \\
-0.625 \\
0.375 \\
\end{bmatrix}.\] Thus,\[ x' = y - \left({v^T y \over 1 + v^T z}\right) z\] This implies \[x' = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix} \frac{0.25}{1-0.625} \begin{bmatrix}
0.125 \\
-0.625 \\
0.375 \\
\end{bmatrix} =\begin{bmatrix}
1 \\
-1 \\
1 \\
\end{bmatrix},\] which is indeed the correct solution.
1 & 2 & 3 \\
1 & 4 & 9 \\
4 & 5 & 7 \\
\end{bmatrix}x = \begin{bmatrix}
2 \\
4 \\
6 \\
\end{bmatrix}.\] The solution of this equation is,\[x = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix}.\] Now let us suppose we wanted to solve a similar problem ( \(A'x' = b\) )with a slightly perturbed matrix,\[A' = \begin{bmatrix}
1 & 2 & 3 \\
1 & 6 & 9 \\
4 & 5 & 7 \\
\end{bmatrix}.\] Notice that this matrix differs from \(A\) in the (2,2) element (6 instead of 4).
The Sherman-Morrison formula tells us to form \(u = [0~1~0]^T, v = [0~~2~~0]^T\), so that \[A' = A + u v^T.\] Hence \[y = x = A^{-1}b = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix},\text{ and } z = A^{-1} u = \begin{bmatrix}
0.125 \\
-0.625 \\
0.375 \\
\end{bmatrix}.\] Thus,\[ x' = y - \left({v^T y \over 1 + v^T z}\right) z\] This implies \[x' = \begin{bmatrix}
0.75 \\
0.25 \\
0.25 \\
\end{bmatrix} \frac{0.25}{1-0.625} \begin{bmatrix}
0.125 \\
-0.625 \\
0.375 \\
\end{bmatrix} =\begin{bmatrix}
1 \\
-1 \\
1 \\
\end{bmatrix},\] which is indeed the correct solution.
No comments:
Post a Comment